Dynamic Complementarities, Efficiency and Nash Equilibria for Populations of Firms and Workers - Accinelli, Elvio (2010)
We consider an economy with two types of firms (innovative and non-innovative) and two types of workers (skilled and unskilled), where workers´ decisions are driven by imitative behavior, and thus the evolution of such an economy depends on the initial distribution of the firms. We show that there exists a continuous of high level steady states and only one low level and asymptotically stable equilibrium. There exists a threshold value on the initial number of firms to be overcome it to located in the basin of attraction of one of the high level equilibrium. We show that in each high level equilibrium there coexists a share of innovative firms with a share of non-innovative firms, and a share of skilled workers (human capital) coexisting with a share of unskilled workers. But if the initial share of innovative firms is lowerthan the threshold value, then the economy evolves to a low level equilibrium wholly composed by non-innovative firms and unskilled workers. Finally, we characterise the equilibria as the evolutionarily stable strategies against a field.